TELKOM UNIVERSITY'S ENVIRONMENTAL COMMUNICATION STRATEGY AS A GREEN CAMPUS - Narawangsa, Panji Fadhila; Dirgantara, Pradipta (eProceedings of Management, 2025)
Environmental problems that are increasing every year with significant levels of pollution and water pollution can disrupt thelearning system and require steps from educators to reduce and create a healthy environment. The emergence of GreenCampus is a university's effort to integrate sustainability principles in all operational and academic aspects. The focus of theresearch is to find out Telkom University's environmental communication strategy in implementing green campus. Qualitativeresearch methods were used with in-depth interviews with key informants, expert informants, and supporting informants, aswell as observation and literature study.The results showed that Telkom University has carried out various environmentalcommunication strategies through various media such as social media and electronic flyers. However, the communication stillfaces challenges related to the level of awareness of the academic community and the lack of formal documentation in theevaluation. Nonetheless, this initiative shows economic potential through circular economy-based waste management andecosystem development. This research recommends improving communication strategies that are more structured and involveall elements of the campus to optimally achieve Green Campus goals.Keywords: Environmental Communication Strategy, Green Campus, Telkom University’s Green Campus, Environment.